If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-3x + -3) = 72 Reorder the terms: -4(-3 + -3x) = 72 (-3 * -4 + -3x * -4) = 72 (12 + 12x) = 72 Solving 12 + 12x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 12x = 72 + -12 Combine like terms: 12 + -12 = 0 0 + 12x = 72 + -12 12x = 72 + -12 Combine like terms: 72 + -12 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| 16x-6=3(5x+3)-3 | | 4a-12+2=2a-10 | | 5(x+8)-2=8(x+3)-1 | | x=11.5+3x | | 19.5/20=x/4 | | 0.065(x+4000)=0.08x+0.04(2000) | | -4x-7=-3 | | -4a+14+9a=5a+2-a | | 5(-3x+1)=-40 | | 6x+5-3(x+1)=9x+7 | | 5k+6=2k+12 | | 7x+3y=44 | | 8/z^2-3/z^3 | | 6(t-6)+8t=7(2t+4)-8 | | 5(-53/4x)=-65/2 | | 28y=39(9y-6) | | 2.94x^2-24.99x-13.23=0 | | (63x^9)/9 | | 5y+1.8-4y=-3.2 | | x=2.5+3y | | x-3+4x=-7x-5x | | 8x-4y-2y+7x+10= | | 0.2(30)=0.4(50+x)-0.8x | | 2/3(8+4x)=104/3 | | 1/7x+3/4x | | 3/5x=1/2x+2 | | b+4b+8=16b+4 | | 4/5n+3-2/3n=1/2-3n | | 8(x+1)-(5x-1)=1 | | X^6+36=100 | | 2x^2-2=7x | | .5y+.5-y=.25 |